The Lutheran Military Chaplaincy in the Finnish Defence Forces’ Organisation Today. A Multi-Method Approach - Liuski, Tiia (Religions, 2021)
The Finnish military chaplains’ work focuses on supporting the conscripts’ ethical functioning ability as well as overall wellbeing of the people in the Finnish Defence Forces. This article gives the military chaplains an opportunity to tell in their own words what kind of issues relate to their perceptions working as a successful religious professional in this unique context. The research was carried out with a multi-method data, that includes an electronic questionnaire and an interview data. The results show that as the military chaplains commit and integrate well to their operational environment, they are also a heterogenous occupational group and manage their work very self-directedly. They appear to be more chaplains than soldiers or special officers, but it does not cause significant professional conflicts. The military chaplains’ profession should be described more as contrasting than conflicting overall. The intensity of their personal vocation and religiosity varies, but it affects considerably to their work motivation. It can be interpreted that military chaplains hold, in a sense, a double vocation towards their work where there is a clerical calling and a mission to work in a military environment.